Digitalization-A Strategic Approach to Promote the Hospitality Industry in Order to Increase Tourism in Sri Lanka with Monetary Gain - Ranasinghe R.A.K.M; Jayawardhana D.M.P.S; Savishka D.K.S; Jayasooriya M.N.N.J; D. I. De Silva; S. M. D. T. H. Dias (International Journal of Engineering and Management Research, 2022)
The purpose of this research was to empower hospitality management and because of that increase tourism attraction. In 2018 direct contribution to GDP was 4.9% It was decrease to 4.3% after the 2019 Easter attack. In 2020 this hugely decreased to 0.8% according to the Tourism Authority of Sri Lanka. Covid 19 impact was affected by that. This study aims at explaining in detail how technology can use to improve the tourism sector. Therefore, the digitalized hotel management system was implemented as a solution for that.